Endogenously-timed Herding and the Synchronization of Investment Cycles - Bernd Süssmuth (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2000)
This paper combines the recent game theoretic approach of endogenous timing of entry to herding models with a macroeconomic model of investment cycles. The integrated description embodies the qualitative results of the myopic herding model in a medium run investment objective of smoothing the capital stock adjustment process. lt features a completely disaggregated structure and bears the potential to synchronize individual cyclic investing behaviors. This synchronization via nonlinear feedback from the aggregate activity can serve as an explanation of the inexistent cancelling of heterogeneous sectoral quasi-cycles. The model offers an explanatory base for the constitution of the observed strong cyclicality of the aggregate investment series by a multitude of different periodicities and phases on the individual level. Finally, based on recent findings of the herding literature, the stabilization potential of third parties' information revelation is conjectured.
urn:nbn:de:bvb:19-epub-24-0
Keywords: D81; D83; E22; E32; 330; herding; investment cycles; nonlinear entrainment